Neurological Recovery after Amantadine Treatment in a Patient with Septic Arthritis: A Case Report - Esra Özayar; İrfan Kenan (Galenos Yayinevi, 2016)
SUMMARY In this case report a patient with septic arthritis who developed impaired consciousness that responded to amantadine sulfate treatment was presented. A 67 years old male patient who had high fever, leukocytosis, hypotension, and generalized organ failure findings after knee prosthesis revision surgery was accepted to intensive care unit. Patient was intubated and connected to mechanical ventilation as he lost consciousness during non-invasive mechanical ventilation. In the follow-up he was diagnosed with bone abscess and was started penicillin according to culture results. Despite of clinical and laboratory resolving of sepsis finding, patient had tonic-clonic seizures especially on the right upper extremity with normal cranial computerized tomography findings. Septic course of the patient improved with antibiotic treatment, while impaired consciousness and seizures continued. Radiological evaluation of the patient was within normal ranges; however he was diagnosed as organic neurological dysfunction that developed secondary to sepsis. Amantadine sulfate 200 mg/day was initiated after neurology department consultation. Neurological suppression and seizures started to improve after the 6th day and completely resolved after the 10th day of the treatment. Patient was discharged from intensive care unit after resolution of septic clinic after 57 days. As a result we believe that amantadine is an efficient agent in treatment of neurological patients with coma and significantly decrease rehabilitation duration